Masyarakat Berkelanjutan Menurut Fritjof Capra dan Inspirasinya - Rau, Renata Stevira (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2025)
This study aims to understand Capra's perspective on a sustainable society while simultaneously drawing inspiration from his efforts to build a harmonious relationship between humans and nature. The research method used is qualitative with a literature study approach. According to Capra, the ecological crisis continues to intensify each year. This crisis is caused by excessive human intervention and exploitation of nature. Such intervention and exploitation are rooted in a worldview that perceives nature as a machine. To address this crisis, a paradigm shift is needed from the mechanistic paradigm to a systemic-holistic paradigm that views humans and nature as an interconnected whole. Arising from this shift, and especially grounded in his philosophy of bioregionalism, Capra proposes the idea of a sustainable society: a society that lives with an awareness of the deep interconnection between humans and nature.This awareness encourages people to embody ecological principles and adopt an ecological lifestyle. Capra's concept of a sustainable society teaches that the ecological crisis can only be resolved when humans acknowledge the crisis, recognize their unity with nature, and develop sustainable living patterns to foster a harmonious relationship between nature and humanity.